The lost symbol - Brown, Dan. (New York : Doubleday & Company, Inc., 2009)
As the story opens, Harvard symbologist Robert Langdon is summoned unexpectedly to deliver an evening lecture in the U.S. Capitol Building. Within minutes of his arrival, however, the night takes a bizarre turn. A disturbing object--artfully encoded with five symbols--is discovered in the Capitol Building. Langdon recognizes the object as an ancient invitation . . . one meant to usher its recipient into a long-lost world of esoteric wisdom.
Keywords: ADVENTURE STORIES -- DETECTIVE -- MYSTERY -- SUSPENSE -- THRILLER -- FICTION